Early detection of anthracycline‐ and trastuzumab‐induced cardiotoxicity: value and optimal timing of serum biomarkers and echocardiographic parameters. (2nd February 2022) - Díaz‐Antón, Belén; Madurga, Rodrigo; Zorita, Blanca; Wasniewski, Samantha; Moreno‐Arciniegas, Andrea; López‐Melgar, Beatriz; Ramírez Merino, Natalia; Martín‐Asenjo, Roberto; Barrio, Patricia; Amado Escañuela, Maximiliano German; Solís, Jorge; Parra Jiménez, Francisco Javier; et al.
Abstract: Aims: To evaluate echocardiographic and biomarker changes during chemotherapy, assess their ability to early detect and predict cardiotoxicity and to define the best time for their evaluation. Methods and results: Seventy‐two women with breast cancer (52 ± 9.8 years) treated with anthracyclines (26 also with trastuzumab), were evaluated for 14 months (6 echocardiograms/12 laboratory tests). We analysed: high‐sensitivity cardiac troponin T, NT‐proBNP, global longitudinal strain (GLS), left ventricle end‐systolic volume (LVESV), left ventricle end‐diastolic volume (LVEDV), and left ventricular ejection fraction (LVEF). Cardiotoxicity was defined as a reduction in LVEF>10% compared with baseline with LVEF<53%. High‐sensitivity troponin T levels rose gradually reaching a maximum peak at 96 ± 13 days after starting chemotherapy ( P < 0.001) and 62.5% of patients presented increased values during treatment. NT‐proBNP augmented after each anthracycline cycle (mean pre‐cycle levels of 72 ± 68 pg/mL and post‐cycle levels of 260 ± 187 pg/mL; P < 0.0001). Cardiotoxicity was detected in 9.7% of patients (mean onset at 5.2 months). In the group with cardiotoxicity, the LVESV was higher compared with those without cardiotoxicity (40 mL vs. 29.5 mL; P = 0.045) at 1 month post‐anthracycline treatment and the decline in GLS was more pronounced (−17.6% vs. −21.4%; P = 0.03). Trastuzumab did not alter serum biomarkers, but it was associated with an increase in LVESV and LVEDV ( P < 0.05). While baseline LVEF was an independent predictor of later cardiotoxicity ( P = 0.039), LVESV and GLS resulted to be early detectors of cardiotoxicity [odds ratio = 1.12 (1.02–1.24), odds ratio = 0.66 (0.44–0.92), P < 0.05] at 1 month post‐anthracycline treatment. Neither high‐sensitivity troponin T nor NT‐proBNP was capable of predicting subsequent cardiotoxicity. Conclusions: One month after completion of anthracycline treatment is the optimal time to detect cardiotoxicity by means of imaging parameters (LVESV and GSL) and to determine maximal troponin rise. Baseline LVEF was a predictor of later cardiotoxicity. Trastuzumab therapy does not affect troponin values hence imaging techniques are recommended to detect trastuzumab‐induced cardiotoxicity.